The Effect of Physical Training at Different Distances Using a Trampoline on Developing Certain Physical and Physiological Abilities for Achieving the 100m Breaststroke in Youth - Kamil, Safieya Ihsan; Sheet, Shahad Haitham (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aimed to design a physical training programme that incorporates different distances to improve specific physical and physiological abilities and utilise trampolines to improve 100m breaststroke performance in young swimmers. Materials and Methods. The researchers employed the experimental method by conducting pre- and post-tests on both the experimental and control groups. The research population consisted of youth swimmers from the Al-Hashd Al-Shaabi Sports Club, specializing in the 100m breaststroke event during the 2022 competitive season. A total of 12 swimmers were selected using a comprehensive sampling approach and were divided into two groups: an experimental group and a control group, with six swimmers in each. The experimental group underwent a physical training program utilizing the trampoline with varied distances, guided by heart rate monitoring, implemented over three training sessions per week for eight weeks. Data analysis was conducted using the SPSS statistical software. Results.The improved results indicate that the specific exercises included in the training program were effective in developing speed, enabling swimmers to complete the race distance as quickly as possible, resulting in better performance. Swimmers with this characteristic can achieve maximum speed in a race, which directly impacts performance. Conclusions. The study concluded that physical training using the trampoline at different distances had a significant positive impact on developing specific physical abilities, which contributed to enhancing 100m breaststroke performance in youth swimmers.